2022
DOI: 10.3389/fphys.2021.767766
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Environmental Chemicals and Natural Products With ABC and SLC Transporters in the Digestive System of Aquatic Organisms

Abstract: An organism’s diet is a major route of exposure to both beneficial nutrients and toxic environmental chemicals and natural products. The uptake of dietary xenobiotics in the intestine is prevented by transporters of the Solute Carrier (SLC) and ATP Binding Cassette (ABC) family. Several environmental chemicals and natural toxins have been identified to induce expression of these defense transporters in fish and aquatic invertebrates, indicating that they are substrates and can be eliminated. However, certain e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 192 publications
(271 reference statements)
0
5
0
Order By: Relevance
“…In fish, as well as in mammals and invertebrates, P-gp can play a role in preventing the absorption of chemicals from the intestinal tract, protecting the organism from potentially harmful substances [53]. P-gp is expressed in the apical membrane of enterocytes, where it actively pumps substrates back into the intestinal lumen, limiting their uptake into the bloodstream [11].…”
Section: P-glycoprotein Tissue Expression and Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fish, as well as in mammals and invertebrates, P-gp can play a role in preventing the absorption of chemicals from the intestinal tract, protecting the organism from potentially harmful substances [53]. P-gp is expressed in the apical membrane of enterocytes, where it actively pumps substrates back into the intestinal lumen, limiting their uptake into the bloodstream [11].…”
Section: P-glycoprotein Tissue Expression and Functionmentioning
confidence: 99%
“…Playing a key role in this chemical defense system in fish is P-gp, which operates in tandem with other defense components. Fish tissues commonly express P-gp alongside other transporters and enzymes, including phase I functionalization enzymes (e.g., cytochrome 450 oxidases), phase II conjugating enzymes (e.g., glutathione S-transferase, sulfotransferase, UDP-glucuronosyltransferase) [75,[92][93][94][95], phase III exporters (e.g., multidrug resistance proteins [MRPs], breast cancer resistance protein [BCRP]) [41,75,93,96]), and solute carrier (SLC) transporters (e.g., organic anion transporting polypeptides [OATPs], organic anion transporters [OATs], organic cation transporters [OCTs], and multidrug and toxin extrusion proteins [MATEs]) [53,97,98]. Although the ABCB (MDR, P-gp) and ABCC (MRP) families of transporters are both referred to as "multidrug resistance proteins", they are distinct classes of transporters that perform different functions in the chemical defense system.…”
Section: P-glycoprotein In the Chemical Defense Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In aquatic organisms, drug transporter inhibition and the resulting chemosensitization of cells and organisms toward toxic environmental chemical bioaccumulation was first described over 30 years ago and has since been confirmed in non-aquatic organisms. [15][16][17] Recent research has shown that environmental chemicals similarly bind and inhibit vertebrate drug transporter function for mouse ABCB1 and tuna ABCB1. 18,19 These so-called transporterinterfering chemicals (or TICs) are typically present at low levels in food, but the sum of individual compounds can reach levels high enough to inhibit drug transporters and trigger consumption advisories based on the risk of developing cancer.…”
mentioning
confidence: 99%
“…Similar challenges exist regarding environmental chemicals. In aquatic organisms, drug transporter inhibition and the resulting chemosensitization of cells and organisms toward toxic environmental chemical bioaccumulation was first described over 30 years ago and has since been confirmed in non‐aquatic organisms 15–17 . Recent research has shown that environmental chemicals similarly bind and inhibit vertebrate drug transporter function for mouse ABCB1 and tuna ABCB1 18,19 .…”
mentioning
confidence: 99%